2013
DOI: 10.4081/jlimnol.2013.e46
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water quality on the feeding ecology of axolotl Ambystoma mexicanum

Abstract: Ambystoma mexicanum, a highly endangered species, is endemic to lake Xochimilco (Mexico City, Mexico)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
4
1
2
Order By: Relevance
“…For instance, the hatching reported by Robles et al (2009) started at day 9 (controlled temperature and photoperiod), while our control individuals started hatching at day 12. Furthermore, different survival/hatching percentage has been reported independently: 75 % found by Chaparro-Herrera et al (2013) in comparison to 100 % observed by Robles et al (2009) and 100 % in the present report. This suggests mild differences in embryo timing that could be related to independent captivity environments (i.e., ambient temperature) (Chaparro-Herrera et al 2018).…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…For instance, the hatching reported by Robles et al (2009) started at day 9 (controlled temperature and photoperiod), while our control individuals started hatching at day 12. Furthermore, different survival/hatching percentage has been reported independently: 75 % found by Chaparro-Herrera et al (2013) in comparison to 100 % observed by Robles et al (2009) and 100 % in the present report. This suggests mild differences in embryo timing that could be related to independent captivity environments (i.e., ambient temperature) (Chaparro-Herrera et al 2018).…”
Section: Discussioncontrasting
confidence: 69%
“…For instance, Ortiz-Ordóñez et al (2016) showed that sediment elutriates from Xochimilco lake were a source of pollutant accumulation with the ability to cause damage at biochemical, cellular and organic levels on A. mexicanum. Considering that axolotls often lay their eggs on the substrate (Chaparro-Herrera et al 2013), it is likely that the accumulation of OPPs in the sediment contributes to the poor survival and conservation of the species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diets of larval Ambystoma can be affected by the quality of the habitat. For example, the diet of Ambystoma ordinarium in Mexico differed between disturbed and undisturbed reaches of a stream (Ruiz-Martínez et al 2014), and wastewater contamination reduces prey consumption by A. mexicanum (Chaparro-Herrera et al 2013). Thus, examining the diets of larval A. rivulare can provide insight into the suitability of the habitat to support the population of salamanders.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several species of Ambystoma in Mexico have been found to be infected with the fungal pathogen Batrachochytrium dendrobatidis (Frías-Alvarez et al 2008). A number of recent studies have focused on the ecology and conservation of the Axolotl, Ambystoma mexicanum (e.g., et al 2004, Bride et al 2008, Contreras et al 2009, Chaparro-Herrera et al 2013 We examined the diet of larval Ambystoma rivulare from a stream on the Volcán Nevado de Toluca in Mexico. Demographic modeling suggests that the egg and larval stages are particularly important for population growth and stability in some Mexican Ambystoma (Zambrano et al 2007).…”
Section: Introductionmentioning
confidence: 99%